2006
DOI: 10.1104/pp.106.081018
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Abscisic Acid Sensitivity and Reduction of Water Consumption in Arabidopsis by Combined Inactivation of the Protein Phosphatases Type 2C ABI1 and HAB1  

Abstract: Abscisic acid (ABA) plays a key role in plant responses to abiotic stress, particularly drought stress. A wide number of ABAhypersensitive mutants is known, however, only a few of them resist/avoid drought stress. In this work we have generated ABA-hypersensitive drought-avoidant mutants by simultaneous inactivation of two negative regulators of ABA signaling, i.e. the protein phosphatases type 2C (PP2Cs) ABA-INSENSITIVE1 (ABI1) and HYPERSENSITIVE TO ABA1 (HAB1). Two new recessive loss-of-function alleles of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
223
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(248 citation statements)
references
References 86 publications
(126 reference statements)
14
223
0
6
Order By: Relevance
“…The data imply that VPS23A also acts upstream of ABI1. abi1-2 is a loss-of-function mutant of ABI1, and hab1-1 is the mutant in hypersensitive to ABA1 (HAB1), another PP2C that cooperates with ABI1 to negatively regulate ABA signaling (Saez et al, 2006). The double mutant abi1-2 hab1-1 exhibited strong hypersensitivity to ABA (Saez et al, 2006).…”
Section: Vps23a Mutant Is Sensitive To Abamentioning
confidence: 99%
See 1 more Smart Citation
“…The data imply that VPS23A also acts upstream of ABI1. abi1-2 is a loss-of-function mutant of ABI1, and hab1-1 is the mutant in hypersensitive to ABA1 (HAB1), another PP2C that cooperates with ABI1 to negatively regulate ABA signaling (Saez et al, 2006). The double mutant abi1-2 hab1-1 exhibited strong hypersensitivity to ABA (Saez et al, 2006).…”
Section: Vps23a Mutant Is Sensitive To Abamentioning
confidence: 99%
“…abi1-2 is a loss-of-function mutant of ABI1, and hab1-1 is the mutant in hypersensitive to ABA1 (HAB1), another PP2C that cooperates with ABI1 to negatively regulate ABA signaling (Saez et al, 2006). The double mutant abi1-2 hab1-1 exhibited strong hypersensitivity to ABA (Saez et al, 2006). Interestingly, the triple mutant vps23a abi1-2 hab1-1 exhibited a more ABA-hypersensitive phenotype than the single mutant vps23a or the double mutant abi1-2 hab1-1 (Figures S2C and S2E), implying that VPS23A might directly or indirectly affect ABI1 and HAB1.…”
Section: Vps23a Mutant Is Sensitive To Abamentioning
confidence: 99%
“…These mutations were isolated 25-years ago by genetic screenings in Arabidopsis, aimed to the identification of ABAinsensitive mutants [27] and the cloning of the mutant loci provided pioneering insights into ABA signaling [28,29,30,31]. Both abi1-1D and abi2-1D are strong ABA-insensitive mutants that show diminished response to ABA in seeds and vegetative tissues, however, analysis of lossof-function alleles indicates that ABI1 and ABI2 gene products, as well as other clade A PP2Cs, are negative regulators of ABA signaling [32,33,34,35]. Since the phenotype of the abi1-1D and abi2-1D dominant alleles is just the opposite of loss-of-function alleles, they can´t represent dominant negative alleles, as it was accurately noted by Robert et al, [36].…”
Section: Abi1-1 G180d Abi2-1 G168d and Hab1 G246d Hypermorphic Enzymesmentioning
confidence: 99%
“…HAB1 binds to and dephosphorylates SnRK2s, especially SnRK2.6 (OST1), and negatively regulates ABA signalling 17,18 . Genetic analyses have suggested that HAB1 is functionally redundant with ABI1 and ABI2 in the regulation of post-germination development and stomatal movement under drought conditions 19,20 . It is apparent that HAB1 is essential in ABA signalling.…”
mentioning
confidence: 99%